Access to essential cancer medicines for children: a comparative mixed-methods analysis of availability, price, and health-system determinants in east Africa. Issue 5 (May 2023) - Petricca, Kadia; Kambugu, Joyce; Githang'a, Jessie; Macharia, William M; Njuguna, Festus; McLigeyo, Angela; Nyangasi, Mary; Orem, Jackson; Kanyamuhunga, Aimable; Laiti, Rehema; Katabalo, Deogratias; Schroeder, Kristin; et al.
Summary: Background: Access to essential childhood cancer medicines is a core determinant of childhood cancer outcomes. Available evidence, although scarce, suggests that access to these medicines is highly variable across countries, particularly in low-income and middle-income countries, where the burden of childhood cancer is greatest. To support evidence-informed national and regional policies for improved childhood cancer outcomes, we aimed to analyse access to essential childhood cancer medicines in four east African countries—Kenya, Rwanda, Tanzania, and Uganda—by determining the availability and price of these medicines and the health system determinants of access. Methods: In this comparative analysis, we used prospective mixed-method analyses to track and analyse the availability and price of essential childhood cancer medicines, investigate contextual determinants of access to childhood cancer medicines within and across included countries, and assess the potential effects of medicine stockouts on treatment. Eight tertiary care hospitals were included, seven were public sites (Kenyatta National Hospital [KNH; Nairobi, Kenya], Jaramogi Oginga Odinga Referral and Teaching Hospital [JOORTH; Kisumu, Kenya], Moi University Teaching and Referral Hospital [MTRH; Eldoret, Kenya], Bugando Medical Centre [BMC; Mwanza, Tanzania], Muhimbili National Hospital [MNH; Dar es Salaam, Tanzania], Butaro Cancer Centre of Excellence [BCCE; Butaro Sector, Rwanda], and Uganda Cancer Institute [UCI; Kampala, Uganda]) and one was a private site (Aga Khan University Hospital [AKU; Nairobi, Kenya]). We catalogued prices and stockouts for 37 essential drugs from each of the eight study siteson the basis of 52 weeks of prospective data that was collected across sites from May 1, 2020, to Jan 31, 2022. We analysed determinants of medicine access using thematic analysis of academic literature, policy documents, and semi-structured interviews from a purposive sample of health system stakeholders. Findings: Recurrent stockouts of a wide range of cytotoxic and supportive care medicines were observed across sites, with highest mean unavailability in Kenya (JOORTH; 48·5%), Rwanda (BCCE; 39·0%), and Tanzania (BMC; 32·2%). Drugs that had frequent stockouts across at least four sites included methotrexate, bleomycin, etoposide, ifosfamide, oral morphine, and allopurinol. Average median price ratio of medicines at each site was within WHO's internationally accepted threshold for efficient procurement (median price ratio ≤1·5). The effect of stockouts on treatment was noted across most sites, with the greatest potential for treatment interruptions in patients with Hodgkin lymphoma, retinoblastoma, and acute lymphocytic leukaemia. Policy prioritisation of childhood cancers, health financing and coverage, medicine procurement and supply chain management, and health system infrastructure emerged as four prominent determinants of access when the stratified purposive sample of key informants (n=64) across all four countries (Kenya n=19, Rwanda n=15, Tanzania n=13, and Uganda n=17) was interviewed. Interpretation: Access to childhood cancer medicines across east Africa is marked by gaps in availability that have implications for effective treatment delivery for a range of childhood cancers. Our findings provide detailed evidence of barriers to access to childhood cancer medicine at multiple points in the pharmaceutical value chain. These data could inform national and regional policy makers to optimise cancer medicine availability and affordability as part of efforts to improve childhood cancer outcomes specific regions and internationally. Funding: American Childhood Cancer Organization, Childhood Cancer International, and the Friends of Cancer Patients Ameera Fund.